Encyclopedia of networked and virtual organizations 2026-02-15T16:50:03+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Putnik, Goran, 1954-; Cruz-Cunha, Maria Manuela, 1964- (Information Science Reference, 2008)

(untitled)
"This book documents the most relevant contributions to the introduction of networked, dynamic, agile, and virtual organizational models; definitions; taxonomies; opportunities; and reference models and architectures. It creates a repository of the main developments regarding the virtual organization, compiling definitions, characteristics, comparisons, advantages, practices, enabling technologies, and best practices"--Provided by publisher